The Effect of Self-Belief on Prosocial Behavior and Religion in Students - Saguni, Fatimah (Manunggal Halim Jaya, 2022)
This study aimed to determine the effect of self-confidence on prosocial behavior in IAIN Palu students and the impact of self-confidence on religiosity in IAIN Palu students. The method used is quantitative. The data analysis uses Multiple Linear Regression correlation, which was carried out with the help of SPSS (Statistical Program For Social Science) for Windows 20.0. With the number of students 30. This study includes three variables, consisting of one independent variable and two dependent variables, namely the independent variable Self-Confidence (X1) and the Prosocial Behavior Bound Variable (Y1) Religiosity (Y2), using a Likert scale as an instrument or collection tool. Data. The results of the research show: (1) The self-confidence variable significantly affects the prosocial attitude of IAIN Palu students. Prosocial behavior reflects the care and concern of a student for other students and is implemented through actions to benefit students. (2) The self-confidence variable significantly affects the religiosity of IAIN Palu students. Self-confidence is an attitude or belief in one's abilities so that in his actions, he is not too anxious, feels free to do things according to his wishes and is responsible for his actions, and is polite in interacting with others.